2020
DOI: 10.1016/j.cell.2019.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Cardiac Sodium Channel

Abstract: Highlights d The structure of the cardiac sodium channel reveals key functional features d The antiarrhythmic drug flecainide blocks the pore below the selectivity filter d The ion selectivity filter and inactivation gate are revealed in atomic detail d An arrhythmia mutation creates a pathogenic gating pore 2 Å in diameter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
482
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(500 citation statements)
references
References 96 publications
16
482
2
Order By: Relevance
“…During this manuscript preparation, cryo-EM structures of a rat Nav1.5 variant that contains truncations in the I-II linker, the II-III linker, and the Cterminus was reported in complex with TTX and flecainide, a class Ic antiarrhythmic drug (34). There are only two overlapping points between the published paper and our present study, the molecular basis for TTX-resistance and the lack of β1 association.…”
Section: Discussionmentioning
confidence: 53%
“…During this manuscript preparation, cryo-EM structures of a rat Nav1.5 variant that contains truncations in the I-II linker, the II-III linker, and the Cterminus was reported in complex with TTX and flecainide, a class Ic antiarrhythmic drug (34). There are only two overlapping points between the published paper and our present study, the molecular basis for TTX-resistance and the lack of β1 association.…”
Section: Discussionmentioning
confidence: 53%
“…NavMs and hNav1.1 exhibit similar ion flux and conductance properties, and as well as very similar binding affinities for a wide range of sodium channel-specific drugs (Bagneris et al, 2014). Structure/function/drug-binding studies using some of the other prokaryotic sodium channels have also showed their comparability to hNavs for drug binding (Payandeh et al, 2011;Jiang et al, 2019), and they too have been used for drug discovery projects (Martin & Corry, 2014;Ouyang et al, 2007), although their structures tend to be of lower resolution than those of NavMs. Much of the focus of this study has been on comparisons of NavMs with hNav1.2 and hNav1.1, as these are the sodium channels primarily found in human central nervous system tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Structural studies lately confirmed that pore opening provides a cytoplasmic entryway for tetrabutylammonium and “ball peptide” to gain access to central cavity sites below the selectivity filter and inner pore sites, ultimately leading to blockage of ion permeation (Zhou et al, 2001a). Moreover, Br-verapamil and flecainide, two drugs widely used for treating arrhythmias, respectively reach an analogous site in Ca v Ab and Nav1.5 via open pore and occlude the ion-conduction pathway (Tang et al, 2016; Jiang et al, 2019).…”
Section: The “Resolution Revolution” Led To Breakthrough In Trpv1 Structural Biologymentioning
confidence: 99%